Simulation of the Industrial Oil Adsorption Purification Process for Automation Tasks. (14th October 2022) - Yaroshchuk, Liudmyla; Tiurina, Yevheniia
Abstract : Objective reasons associated with an increase of transport quantity and the volume of industrial goods and energy service production lead to the accumulation of used oils and greases. These substances can be reused in the case of their purification. Such resource saving is facilitated by the development of technologies, in particular, adsorption purification and efficient systems for their automation. The article carried out a detailed analysis of the continuous adsorption purification technological system and indicated its significant differences from the point of view of control systems with special preparation of raw materials. The conclusion about the presence of nonstationarity and stochasticity sources of continuous adsorption as a control object is substantiated, which made it possible to impose requirements on the properties of the control model. The existing methods of adsorption mathematical description are analyzed within their use for continuous control. Structures of dynamic models based on a combination of analytical and experimental methods are proposed. Analytical models are based on mass balances of substances, known forms of approximations for describing equilibrium conditions and adsorption kinetics are studied, and experimental and statistical modeling is carried out to determine possible structures of the connection between technological variables during control. A structural-parametric scheme of the model and a scheme for its adaptation in control systems have been formed. An example of an adsorption simulation model formation using MATLAB + Simulink is shown. The results can be used to develop software for control systems of continuous adsorption and to test control algorithms.